Phase-locked and non-phase-locked EEG responses to pinprick stimulation before and after experimentally-induced secondary hyperalgesia. Issue 8 (August 2017) - van den Broeke, Emanuel N.; de Vries, Bart; Lambert, Julien; Torta, Diana M.; Mouraux, André
Highlights: Pinprick stimuli elicit a low-frequency EEG response and a reduction of alpha-band oscillations. Secondary hyperalgesia is associated with an increase of the low-frequency EEG response. Time-frequency analysis is useful for identifying this increase in low-frequency EEG response. Abstract: Objective: Pinprick-evoked brain potentials (PEPs) have been proposed as a technique to investigate secondary hyperalgesia and central sensitization in humans. However, the signal-to-noise (SNR) of PEPs is low. Here, using time-frequency analysis, we characterize the phase-locked and non-phase-locked EEG responses to pinprick stimulation, before and after secondary hyperalgesia. Methods: Secondary hyperalgesia was induced using high-frequency electrical stimulation (HFS) of the left/right forearm skin in 16 volunteers. EEG responses to 64 and 96 mN pinprick stimuli were elicited from both arms, before and 20 min after HFS. Results: Pinprick stimulation applied to normal skin elicited a phase-locked low-frequency (<5 Hz) response followed by a reduction of alpha-band oscillations (7–10 Hz). The low-frequency response was significantly increased when pinprick stimuli were delivered to the area of secondary hyperalgesia. There was no change in the reduction of alpha-band oscillations. Whereas the low-frequency response was enhanced for both 64 and 96 mN intensities, PEPs analyzed in the time domain were only significantly enhanced for the 64 mN intensity. Conclusions: Time-frequency analysis may be more sensitive than conventional time-domain analysis in revealing EEG changes associated to secondary hyperalgesia. Significance: Time-frequency analysis of PEPs can be used to investigate central sensitization in humans.